2012
DOI: 10.1002/bjs.8813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 30-day, 90-day and in-hospital postoperative mortality for eight different cancer types

Abstract: The 30-day definition is recommended as an international standard because it includes the great majority of surgery-related deaths and is not subject to discharge procedures. The 90-day definition, however, captures mortality from multiple causes; although this may be of less interest to surgeons, the data may be valuable when providing information to patients before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 21 publications
6
87
0
Order By: Relevance
“…Furthermore, the improved ability to support patients with severe postoperative complications may have resulted in delayed mortality beyond the 30-day period. However, extending the time window of postoperative mortality risks until 90 days postoperatively may include patients who die from progressive disease [21]. In our study, both elderly patients and resected patients with metastatic disease showed an elevated 90-day mortality risk.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the improved ability to support patients with severe postoperative complications may have resulted in delayed mortality beyond the 30-day period. However, extending the time window of postoperative mortality risks until 90 days postoperatively may include patients who die from progressive disease [21]. In our study, both elderly patients and resected patients with metastatic disease showed an elevated 90-day mortality risk.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, possibly more elderly patients in the Netherlands could benefit from pancreatic surgery [2,10]. Several studies on surgical risks of patients with gastrointestinal cancers showed that postoperative mortality prolonged beyond the 30-day postoperative period [3,[19][20][21]. In a recent study, a doubling of the 30-day mortality rate after pancreatic surgery was found by 90 days postoperative [3].…”
Section: Discussionmentioning
confidence: 94%
“…Mortality after 30 days and after hospital discharge up to 90 days postoperatively was studied using the Rotterdam Cancer Registry; 3.6% 30-day mortality and 6.8% 90-day mortality was reported between 2006 and 2008. 19 Some of the decrease in 30-day mortality seen in the current study likely has resulted from the increased ability to support critically ill patients postoperatively, delaying some postoperative mortality beyond the traditional 30-day period often used to report operative mortality. A broadened definition of operative mortality to include 30-day and in-hospital mortality during the initial admission will still not capture patients discharged to hospice care more than 30 days after surgery or who die after discharge.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore we recommend usage of 30-daymortality. This seems the most reliable outcome parameter, because it includes the majority of surgery-related deaths and is not subject to discharge procedures [38]. However, because of the retrospective nature of many of the included studies this was not feasible.…”
Section: Limitationsmentioning
confidence: 97%